Positive electrode plate for lithium ion secondary battery and method for manufacturing the positive electrode plate for lithium ion secondary battery
By adding suitable lithium salts and organic acids to the positive electrode mixture of lithium-ion secondary batteries, the problem of reducing battery performance by fluoride is solved, and better battery performance and safety is achieved.
Patent Information
- Application Number
- JP2021209927
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-23
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-12-23
AI Technical Summary
Fluoride is generated in the non-aqueous electrolyte of lithium-ion secondary batteries, causing the positive electrode active material to be attacked by hydrofluoric acid, thereby reducing battery performance.
The lithium salt is added to the cathode mixture, and reacts with an organic acid with an acid dissociation constant of 3.15 or higher to form a relatively weak acid to consume the resulting fluoride.
By consuming fluoride, preventing its attack on the positive electrode active material, improving battery performance, and evaporation of organic acids and foam formation in short circuit or overheating, increasing resistance and cutting off current, improving safety.
Smart Images

Figure 0007662506000006 
Figure 0007662506000007 
Figure 0007662506000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a lithium ion secondary battery. Positive plate and lithium ion secondary batteries Positive plate The present invention relates to a method for producing the above-mentioned product. [Background technology]
[0002] Conventionally, in lithium ion secondary batteries, a composite paste containing a positive electrode active material is applied to a substrate serving as a current collector to form a positive electrode composite layer on the substrate, that is, a positive electrode is generally formed. For example, Patent Document 1 discloses a configuration in which the components of the composite paste are adjusted to suppress thickening due to changes over time and ensure high low-temperature output characteristics. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-164960 A Summary of the Invention [Problem to be solved by the invention]
[0004] In general, a fluorine-based non-aqueous electrolyte is used in a lithium-ion secondary battery. Therefore, hydrogen fluoride, i.e., hydrofluoric acid, may be generated in the electrolyte due to potential changes accompanying charging and discharging, or due to the inclusion of moisture. This hydrogen fluoride attacks and modifies the active material in the positive electrode mixture, which may result in a decrease in the battery performance. [Means for solving the problem]
[0005] The lithium ion secondary battery that solves the above problems contains, in a positive electrode mixture containing a positive electrode active material, a lithium salt that reacts with hydrogen fluoride generated in the electrolyte to generate an organic acid that is a relatively weak acid relative to hydrogen fluoride and has an acid dissociation constant of 3.15 or more.
[0006] According to the above-mentioned configuration, the hydrogen fluoride generated in the electrolyte can be consumed by the weak acid liberation reaction of the lithium salt contained in the positive electrode mixture, and this makes it possible to suppress the denaturation of the positive electrode active material due to the attack of hydrogen fluoride, thereby ensuring excellent battery performance.
[0007] In particular, the use of a lithium salt does not inhibit the battery reaction, thereby ensuring better battery performance. Furthermore, when the lithium ion secondary battery is in an overheated state, for example, when a short circuit occurs between the positive electrode and the negative electrode, the organic acid, which is the product of the weak acid liberation reaction, vaporizes and becomes bubbles, which envelop the positive electrode active material. This inhibits charge transfer to the positive electrode active material, thereby increasing its electrical resistance. This cuts off the current, thereby suppressing further temperature rise. As a result, high safety can be ensured.
[0008] In the lithium ion secondary battery that solves the above problems, the concentration of the lithium salt contained in the positive electrode mixture is preferably 10 ppm or more and 5000 ppm or less. According to the above-mentioned configuration, the battery performance can be effectively improved without inhibiting the battery reaction.
[0009] In the lithium ion secondary battery that solves the above problems, the electrolyte preferably contains a fluorine compound as an additive. In other words, the use of such a fluorine-based additive can improve the battery performance, but at the same time, it also tends to generate hydrogen fluoride in the electrolyte. Therefore, by applying the additive to such a configuration, a more significant effect can be obtained.
[0010] In the lithium ion secondary battery that solves the above problems, it is preferable that the number of fluorine atoms contained in one molecule of the fluorine compound serving as the additive is 1, the additive is added to the electrolyte in an amount of 0.01 mol / L or more and 0.3 mol / L or less, and the concentration of the lithium salt contained in the positive electrode mixture is 80 ppm or more and 3000 ppm or less.
[0011] According to the above-mentioned configuration, when the electrolyte contains a fluorine-based additive, the battery performance can be improved more effectively. In the lithium ion secondary battery that solves the above problems, the concentration of the lithium salt is preferably 100 ppm or more.
[0012] According to the above configuration, the battery performance can be improved more effectively. In the lithium ion secondary battery that solves the above problems, the concentration of the lithium salt contained in the positive electrode mixture is preferably 500 ppm or more and 3000 ppm or less.
[0013] According to the above configuration, the battery performance can be improved more effectively. In the lithium ion secondary battery that solves the above problems, it is preferable that the boiling point of the organic acid is equal to or lower than the melting point of the separator.
[0014] According to the above configuration, when the temperature rises excessively, the current can be cut off before the separator melts and the positive and negative electrodes come into surface contact with each other, thereby suppressing a further temperature rise, and thus ensuring an even higher level of safety.
[0015] In the lithium ion secondary battery that solves the above problems, the organic acid is preferably acetic acid. That is, since the acid dissociation constant of acetic acid is 3.15 or more, the weak acid liberation reaction with hydrogen fluoride generated in the electrolyte proceeds quickly, and this effectively suppresses the denaturation of the positive electrode active material due to the attack of hydrogen fluoride, thereby ensuring excellent battery performance.
[0016] In addition, since acetic acid has a relatively low boiling point, it is easily vaporized when the temperature rises excessively. Furthermore, the vaporized acetic acid turns into bubbles that envelop the positive electrode active material, increasing the electrical resistance, and cutting off the current, thereby suppressing further temperature rise. As a result, high safety can be ensured.
[0017] A method for manufacturing a lithium ion secondary battery that solves the above problems is a method for manufacturing a lithium ion secondary battery in which a composite paste containing a positive electrode active material is applied to a substrate serving as a current collector to form a positive electrode composite layer on the substrate, and preferably includes a step of making the composite paste contain a lithium salt that reacts with hydrogen fluoride generated in the electrolyte to produce an organic acid that is a relatively weak acid relative to hydrogen fluoride and has an acid dissociation constant of 3.15 or more.
[0018] According to the above-mentioned configuration, the hydrogen fluoride generated in the electrolyte can be consumed by the weak acid liberation reaction of the lithium salt contained in the positive electrode mixture, and this makes it possible to suppress the denaturation of the positive electrode active material due to the attack of hydrogen fluoride, thereby ensuring excellent battery performance.
[0019] The method for producing a lithium ion secondary battery that solves the above problems preferably includes a step of adding the organic acid to the composite paste and reacting it with excess lithium in the positive electrode active material to produce the lithium salt when producing the composite paste.
[0020] According to the above configuration, by utilizing the neutralization reaction between the excess lithium in the positive electrode active material and the organic acid added to the composite paste, a lithium ion secondary battery can be easily manufactured in which a lithium salt that reacts with hydrogen fluoride generated in the electrolyte is contained in the positive electrode composite.
[0021] Furthermore, the lithium salt in the positive electrode mixture is in a state of being approximately uniformly present as fine particles around the positive electrode active material, and this allows the lithium salt to efficiently react with hydrogen fluoride, which attacks the positive electrode active material.
[0022] Furthermore, the organic acid, which is a product of the weak acid liberation reaction, is present in the vicinity of the positive electrode active material. Therefore, when the temperature rises excessively, the vaporized organic acid quickly wraps around the positive electrode active material. This makes it possible to more appropriately suppress further temperature rise.
[0023] In addition, the fine particles of lithium salt present around the positive electrode active material improve the slipperiness between the positive electrode active materials contained in the positive electrode mixture, which reduces the pressure acting on the positive electrode active material when shaping the electrode body.
[0024] In the manufacturing method for a lithium ion secondary battery that solves the above problems, the step of generating the lithium salt is preferably carried out by adding the organic acid in an amount of 0.1 equivalent or more and 3 equivalents or less relative to the positive electrode active material to the composite paste in a state in which the excess lithium is present in the positive electrode active material in a concentration range of 0.03 wt % or more and 0.5 wt % or less relative to the positive electrode active material.
[0025] According to the above-mentioned configuration, a lithium salt having a preferable concentration can be produced in the positive electrode mixture. Effect of the Invention
[0026] According to the present invention, it is possible to suppress the deterioration of battery performance caused by hydrogen fluoride produced in the electrolyte. [Brief description of the drawings]
[0027] [Figure 1] FIG. 1 is a perspective view of a lithium-ion secondary battery. [Diagram 2] Exploded view of the electrode body. [Diagram 3] FIG. 1 is a side view of a lithium-ion secondary battery. [Figure 4] FIG. 4 is an explanatory diagram illustrating a reaction between lithium acetate contained in a positive electrode mixture layer and hydrogen fluoride produced in an electrolyte solution. [Diagram 5] 4 is a flowchart showing a method for producing a positive electrode mixture layer containing lithium acetate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Hereinafter, an embodiment of a lithium ion secondary battery and a method for manufacturing the same will be described with reference to the drawings. 1, the lithium ion secondary battery 1 includes an electrode assembly 10 in which a positive electrode 3, a negative electrode 4, and a separator 5 are integrated, and a case 20 that houses the electrode assembly 10. The lithium ion secondary battery 1 of this embodiment has a configuration in which the electrode assembly 10 in the case 20 is impregnated with a non-aqueous electrolyte solution (not shown).
[0029] More specifically, in the lithium ion secondary battery 1 of this embodiment, the positive electrode 3, the negative electrode 4, and the separator 5 are laminated with a sheet-like outer shape. Then, by winding up the laminate of the positive electrode 3, the negative electrode 4, and the separator 5, an electrode body 10 is formed in which the positive and negative electrodes and the separators 5 are alternately arranged in the radial direction with the separator 5 sandwiched between the positive electrode 3 and the negative electrode 4.
[0030] The case 20 of this embodiment includes a case body 21 having a flat, substantially rectangular box shape, and a lid member 22 that closes an open end 21x of the case body 21. The electrode body 10 of this embodiment has a flat outer shape that corresponds to the box shape of the case 20.
[0031] More specifically, as shown in FIG. 2, in the lithium ion secondary battery 1 of this embodiment, the positive electrode 3 and the negative electrode 4 each have a configuration as an electrode sheet 35 including a current collector 31 having a sheet-like outer shape and an electrode active material layer 32 laminated on this current collector 31.
[0032] Specifically, for the electrode sheet 35P for the positive electrode 3, a composite paste 37P containing a lithium transition metal oxide serving as a positive electrode active material is applied to a substrate 36P made of aluminum or the like that constitutes the positive electrode current collector 31P. For the electrode sheet 35N for the negative electrode 4, a composite paste 37N containing a carbon-based material serving as a negative electrode active material is applied to a substrate 36N made of copper or the like that constitutes the negative electrode current collector 31N. Furthermore, each of these composite pastes 37P and 37N contains a binder. In the lithium ion secondary battery 1 of this embodiment, the composite pastes 37P and 37N are dried to form the corresponding positive electrode active material layer 32P and negative electrode active material layer 32N for the positive and negative electrode sheets 35P and 35N, respectively.
[0033] Furthermore, in the lithium ion secondary battery 1 of this embodiment, the positive and negative electrode sheets 35P, 35N are each shaped into a belt-like shape. The electrode body 10 of this embodiment is configured such that the positive and negative electrode sheets 35P, 35N, which are stacked with the separator 5 sandwiched therebetween, are wound around a winding axis L extending in the width direction of the belt-like shape (the left-right direction in FIG. 2).
[0034] 2, the separator 5 and each electrode sheet 35 are wound in such a manner that the electrode sheet 35P constituting the positive electrode 3 is wound inward. However, this figure is one example showing the structure of the electrode body 10, and the separator 5 and each electrode sheet 35 may be wound in such a manner that the electrode sheet 35N constituting the negative electrode 4 is wound inward. This determines whether the electrode sheet 35 arranged on the outermost shell of the electrode body 10 is the electrode sheet 35P constituting the positive electrode 3 or the electrode sheet 35N constituting the negative electrode 4.
[0035] 1 to 3, the cover member 22 of the case 20 is provided with a positive electrode terminal 38P and a negative electrode terminal 38N that protrude to the outside of the case 20. Furthermore, each electrode sheet 35 has an uncoated portion 39 in which the electrode active material layer 32 is not formed on the current collector 31. The lithium ion secondary battery 1 of this embodiment is configured such that the electrode sheet 35P constituting the positive electrode 3 and the positive electrode terminal 38P are electrically connected, and the electrode sheet 35N constituting the negative electrode 4 and the negative electrode terminal 38N are electrically connected, utilizing the uncoated portion 39.
[0036] Specifically, the electrode body 10 of this embodiment is housed in the case 20 with its winding axis L aligned along the longitudinal direction (left-right direction in FIG. 1) of the cover member 22, which is an elongated, generally rectangular plate. Furthermore, in this state, an uncoated portion 39P of an electrode sheet 35P constituting the positive electrode 3 is connected to a positive electrode terminal 38P via a connecting member 40P. Similarly, an uncoated portion 39N of an electrode sheet 35N constituting the negative electrode 4 is connected to a negative electrode terminal 38N via a connecting member 40N.
[0037] Furthermore, an electrolyte solution 41 is poured into the case 20. In the lithium ion secondary battery 1 of this embodiment, a fluorine-based electrolyte solution 41 in which a lithium salt serving as a supporting salt is dissolved in an organic solvent is used. Thus, the lithium ion secondary battery 1 of this embodiment is configured such that the electrolyte solution 41 is impregnated into the electrode body 10 sealed in the case 20.
[0038] (Function to consume hydrogen fluoride generated in the electrolyte) Next, the function of consuming hydrogen fluoride generated in the electrolyte applied to the lithium ion secondary battery 1 of this embodiment will be described.
[0039] As shown in FIG. 4, in the lithium ion secondary battery 1 of this embodiment, the positive electrode 3 is formed by a positive electrode composite material 51 containing a positive electrode active material 50. The positive electrode composite material 51 forms a positive electrode composite material layer 52 as a positive electrode active material layer 32P by applying a composite material paste 37P containing the positive electrode active material 50 on a base material 36P as described above (see FIG. 2). In the lithium ion secondary battery 1 of this embodiment, the positive electrode composite material 51 contains lithium acetate 53 together with the positive electrode active material 50 and a binder not shown. Furthermore, in the lithium ion secondary battery 1 of this embodiment, the lithium acetate 53 reacts with hydrogen fluoride 54 generated in the electrolyte 41, that is, hydrofluoric acid. The lithium ion secondary battery 1 of this embodiment has a function of consuming hydrogen fluoride 54 generated in the electrolyte 41 due to potential changes accompanying charging and discharging, the inclusion of moisture, and the like.
[0040] More specifically, the process by which hydrogen fluoride 54 is produced in the electrolyte 41 can be represented by, for example, the following reaction formulas.
[0041] [ka] In the lithium-ion secondary battery 1 of the present embodiment, hydrogen fluoride 54 produced in the electrolyte 41 reacts with lithium acetate 53 in the positive electrode mixture 51 to produce acetic acid 55 and lithium fluoride 56, as shown in the following reaction formula.
[0042] [ka] That is, acetic acid 55 is an organic acid 57 having an acid dissociation constant (pKa) of 3.15 or more, which makes it a weak acid relative to hydrogen fluoride 54. The lithium ion secondary battery 1 of this embodiment is configured such that the hydrogen fluoride 54 in the electrolyte solution 41 is consumed as the weak acid liberation reaction between the lithium acetate 53 as the lithium salt 58 and the hydrogen fluoride 54 proceeds.
[0043] More specifically, in the lithium ion secondary battery 1 of this embodiment, the lithium acetate 53 in the positive electrode mixture 51 is present approximately uniformly as fine particles around the positive electrode active material 50. The concentration of the lithium acetate 53 contained in the positive electrode mixture 51 is preferably, for example, 10 ppm to 5000 pp. And, more preferably, the concentration of the lithium acetate 53 is desirably 500 ppm to 3000 ppm. In this case, the word "to" indicates a range including the "lower limit value and upper limit value" written before and after it (the same applies hereinafter).
[0044] In other words, the lower limit of the concentration of lithium acetate 53 contained in the positive electrode mixture 51 can be, for example, 10 ppm or more, or 500 ppm, and the upper limit of the concentration can be, for example, 3000 ppm or less, or 5000 ppm or less.
[0045] (Manufacturing method) Next, a manufacturing method for forming positive electrode mixture layer 52 containing lithium acetate 53 as described above will be described.
[0046] 5, in the lithium ion secondary battery 1 of this embodiment, first, a composite paste 37P is prepared (step 101), and then, the composite paste 37P is applied to a base material 36P (step 102). Then, the composite paste 37P applied to the base material 36P is dried to produce an electrode sheet 35P for the positive electrode 3 having a positive electrode composite layer 52 that becomes the positive electrode active material layer 32P (step 103).
[0047] In the lithium ion secondary battery 1 of this embodiment, when the composite paste 37P is prepared in step 101, acetic acid 55 is added to the composite paste 37P. The added acetic acid 55 reacts with excess lithium (not shown) present in the positive electrode active material 50, thereby generating lithium acetate 53 in the composite paste 37P, which reacts with hydrogen fluoride 54 generated in the electrolyte 41.
[0048] Specifically, the excess lithium in the positive electrode active material 50 exists in the form of lithium hydroxide (LiOH). In the lithium ion secondary battery 1 of this embodiment, lithium acetate 53 is produced in the composite paste 37P by a neutralization reaction with acetic acid 55 shown below.
[0049] [ka] More specifically, in the lithium ion secondary battery 1 of this embodiment, when acetic acid 55 is added to the composite paste 37P, the positive electrode active material 50 is adjusted to have excess lithium present in the positive electrode active material 50 in a concentration range of, for example, 0.03 wt % to 0.5 wt %. The amount of acetic acid 55 added to the composite paste 37P is adjusted to, for example, 0.1 equivalent to 3 equivalents relative to the positive electrode active material 50. Note that "equivalent" refers to "molar equivalent".
[0050] In other words, when acetic acid 55 is added to composite paste 37P, the amount of excess lithium present in positive electrode active material 50 is adjusted to 0.03 wt % or more and 0.5 wt % or less with respect to positive electrode active material 50. The amount of acetic acid 55 added is adjusted to 0.1 equivalents or more and 3 equivalents or less.
[0051] In the lithium ion secondary battery 1 of this embodiment, in the drying process of step 103, the composite paste 37P applied onto the base material 36P is heated to a temperature equal to or higher than the boiling point of acetic acid 55, i.e., 118° C. or higher. In this way, the lithium ion secondary battery 1 of this embodiment is configured to remove the acetic acid 55 remaining in the composite paste 37P after the reaction with the excess lithium in step 101.
[0052] Next, the operation of this embodiment will be described. That is, in the lithium ion secondary battery 1 of the present embodiment, when hydrogen fluoride 54 is generated in the electrolyte 41, this hydrogen fluoride 54 reacts with the lithium acetate 53 contained in the positive electrode mixture 51. As a result, the hydrogen fluoride 54 in the electrolyte 41 is consumed.
[0053] Next, the effects of this embodiment will be described. (1) As described above, according to the present embodiment, hydrogen fluoride 54 produced in the electrolyte solution 41 can be consumed by the weak acid liberation reaction of lithium acetate 53 contained in the positive electrode mixture 51. This makes it possible to suppress the denaturation of the positive electrode active material 50 due to the attack of hydrogen fluoride 54, thereby ensuring excellent battery performance.
[0054] (2) In particular, by using lithium acetate 53 as lithium salt 58 in positive electrode mixture 51 that reacts with hydrogen fluoride 54 generated in electrolyte 41, lithium acetate 53 does not inhibit the battery reaction, thereby ensuring excellent battery performance.
[0055] (3) In addition, when the lithium ion secondary battery 1 is in an overheated state, for example, when a short circuit occurs in the electrode body 10, the acetic acid 55, which is a product of the weak acid liberation reaction, vaporizes and becomes bubbles, which encapsulate the positive electrode active material 50. This inhibits charge transfer to the positive electrode active material 50, thereby increasing its electrical resistance. This in turn blocks the current, thereby suppressing further temperature rise. As a result, high safety can be ensured.
[0056] (4) In particular, the boiling point of acetic acid 55 is usually lower than the melting point of separator 5. Therefore, before separator 5 melts and positive electrode 3 and negative electrode 4 come into surface contact with each other, the current can be cut off to suppress a further increase in temperature. This further ensures high safety.
[0057] (5) When producing composite paste 37P, acetic acid 55 is added to this composite paste 37P. Then, this added acetic acid 55 reacts with excess lithium in positive electrode active material 50, thereby producing lithium acetate 53 in composite paste 37P.
[0058] According to the above configuration, by utilizing the neutralization reaction between the excess lithium in the positive electrode active material 50 and the acetic acid 55 added to the composite paste 37P, it is possible to easily manufacture a lithium ion secondary battery 1 in which the positive electrode composite 51 contains lithium salt 58.
[0059] Moreover, the lithium acetate 53 in the positive electrode mixture 51 is in a state of being present approximately uniformly as fine particles around the positive electrode active material 50. This allows the lithium acetate 53 to react efficiently with hydrogen fluoride 54, which attacks the positive electrode active material 50.
[0060] Furthermore, acetic acid 55, which is a product of the weak acid liberation reaction, is present in the vicinity of the positive electrode active material 50. Therefore, when the temperature rises excessively, the vaporized acetic acid 55 quickly wraps around the positive electrode active material 50. This makes it possible to more appropriately suppress a further temperature rise.
[0061] In addition, the lithium acetate particles 53 present around the positive electrode active material 50 improve the slipperiness between the positive electrode active materials 50 contained in the positive electrode mixture 51. This makes it possible to reduce the pressure acting on the positive electrode active material 50 when shaping the electrode body 10.
[0062] (6) When the composite paste 37P applied onto the base material 36P is dried, the composite paste 37P is heated to a temperature equal to or higher than the boiling point of the added acetic acid 55. This makes it possible to easily remove the acetic acid 55 remaining in the composite paste 37P after the reaction with the excess lithium of the positive electrode active material 50 with a simple configuration.
[0063] The above embodiment can be modified as follows: The above embodiment and the following modifications can be combined with each other to the extent that no technical contradiction occurs.
[0064] The present invention may be applied to a configuration in which the electrolyte 41 contains a fluorine compound as an additive. Examples of the fluorine-based additive used in the electrolyte 41 of the lithium ion secondary battery 1 include fluorosulfonic acid (FSO) and fluoroethylene carbide (FEC). The fluorosulfonic acid is added to the electrolyte 41 in the form of a lithium salt, that is, lithium fluorosulfonate. In addition to these additives having one fluorine atom (F) per molecule, the present invention may be applied to a configuration in which a fluorine compound having two fluorine atoms per molecule is used as an additive. Examples of such additives having two fluorine atoms include difluoroethylene carbide (DFEC) and lithium bis(fluorosulfonyl)imide (LFSI).
[0065] That is, the use of such a fluorine-based additive can improve the battery performance. However, the tradeoff is that hydrogen fluoride 54 is more likely to be generated in the electrolyte solution 41. In this case, the process by which hydrogen fluoride 54 is generated in the electrolyte solution 41 can be represented by, for example, the following reaction formulas.
[0066] [ka] In consideration of this, in the lithium ion secondary battery 1 using such a fluorine-based additive, lithium acetate 53 is contained in the positive electrode mixture 51, as in the above embodiment. Then, by reacting this lithium acetate 53 with hydrogen fluoride 54 generated in the electrolyte 41, it is possible to effectively suppress the denaturation of the positive electrode active material 50 due to the attack of the hydrogen fluoride 54, and ensure excellent battery performance.
[0067] Specifically, when using a fluorine compound having one fluorine atom in one molecule, such as the above-mentioned "FSO" or "FEC," it is advisable to add, for example, 0.01 mol / L to 0.3 mol / L of such a fluorine-based additive to the electrolyte solution 41. In this case, the concentration of the lithium acetate 53 contained in the positive electrode mixture 51 is preferably, for example, 80 ppm or more. More preferably, the concentration of the lithium acetate 53 is desirably 100 ppm to 3000 ppm.
[0068] In other words, in this case, the lower limit of the concentration of lithium acetate 53 contained in the positive electrode composite 51 can be, for example, 80 ppm or more, or 100 ppm or more. The upper limit of the concentration can be, for example, 3000 ppm or less. The lower limit of the concentration can be, for example, 500 ppm or more, similar to the case where no fluorine-based additive is contained. Then, by using the value in the case where the electrolyte solution 41 does not contain a fluorine compound as an additive, the upper limit of the concentration can be extended to, for example, 5000 ppm or less, and the lower limit can be extended to, for example, 10 ppm.
[0069] When using a fluorine compound having two fluorine atoms in one molecule, such as the above-mentioned "DFEC" or "LFSI," it is advisable to appropriately adjust the concentration of lithium acetate 53 contained in the positive electrode mixture 51. This allows the lithium acetate 53 to react with hydrogen fluoride 54 generated in the electrolyte 41 efficiently without inhibiting the battery reaction.
[0070] In the above embodiment, when the composite paste 37P is generated, acetic acid 55 is added and reacted with excess lithium in the positive electrode active material 50 to generate lithium acetate 53 in the composite paste 37P. However, the present invention is not limited to this, and when the composite paste 37P is generated, fine particle lithium acetate 53 may be mixed in. In addition, a method of reacting acetic acid 55 added to the composite paste 37P with excess lithium in the positive electrode active material 50 and a method of mixing fine particle lithium acetate 53 into the composite paste 37P may be used in combination.
[0071] In the above embodiment, lithium acetate 53 is included in the positive electrode mixture 51. However, this is not limiting, and as long as a weak acid liberation reaction with hydrogen fluoride 54 generated in the electrolyte 41 proceeds, the lithium salt 58 included in the positive electrode mixture 51 does not necessarily have to be lithium acetate 53. In other words, the lithium salt 58 included in the positive electrode mixture 51 may be any that reacts with hydrogen fluoride 54 generated in the electrolyte 41 to generate organic acid 57 having an acid dissociation constant of 3.15 or more and that is a weak acid relative to hydrogen fluoride 54.
[0072] Moreover, it is preferable that the boiling point of organic acid 57 generated by a weak acid liberation reaction between hydrogen fluoride 54 generated in electrolyte 41 and lithium salt 58 contained in positive electrode mixture 51 is equal to or lower than the melting point of separator 5. By adopting such a configuration, when the temperature rises excessively, before separator 5 melts, organic acid 57 vaporizes and forms bubbles that envelop positive electrode active material 50. This makes it possible to prevent the generation of a large current due to surface contact between positive electrode 3 and negative electrode 4, ensuring high safety.
[0073] Furthermore, in the above embodiment, the electrode body 10 is formed by winding the positive and negative electrode sheets 35P, 35N stacked with the separator 5 sandwiched therebetween. However, the present invention is not limited to this, and may be applied to a configuration having a stacked electrode body 10 having a plurality of electrode plate groups.
[0074] The terminal shapes of the positive electrode terminal 38P and the negative electrode terminal 38N are not limited to the shapes shown in FIG. 1 and may be changed arbitrarily. EXAMPLES
[0075] Examples will be described below to more specifically explain the configuration and effects of the present invention, but the present invention is not limited to these examples.
[0076] [Table 1] In Table 1, the "acid" column indicates the type, physical properties, and amount of organic acid 57 added to composite paste 37P when preparing this composite paste 37P. The "active substance" column indicates the amount of excess lithium (LiOH amount) in positive electrode active material 50, and the "in composite" column indicates the concentration of lithium salt 58 contained in positive electrode composite 51. The "drying temperature" column indicates the temperature at which composite paste 37P applied to base material 36P is dried, and in each of the examples and comparative examples in Table 1, this "drying temperature" is uniformly set to 180°C.
[0077] In Table 1, the column "electrolyte additive" indicates the presence or absence of a fluorine-based additive and the type of the fluorine compound added to the electrolyte 41. The columns "initial resistance," "capacity retention rate after 1000 cycles," "resistance increase rate after 1000 cycles," and "nail penetration test results" each indicate the battery performance of the lithium ion secondary battery 1.
[0078] In Table 1, the value in the "initial resistance" column is preferably closer to "100%". The value in the "capacity maintenance rate after 1000 cycles" column is also preferably closer to "100%". However, due to their nature, the value in the "initial resistance" column is preferably smaller, and the value in the "capacity maintenance rate after 1000 cycles" column is preferably larger. The value in the "resistance increase rate after 1000 cycles" column is preferably smaller.
[0079] The "nail penetration test" is a non-normal mode test in which a metal "nail" is thrust into a "cell," which is the basic unit of the lithium-ion secondary battery 1, to forcibly short-circuit the positive electrode 3 and the negative electrode 4. In other words, this "nail penetration test" is a test that artificially creates a state that would not normally occur, such as when the lithium-ion secondary battery 1 is damaged by application of a strong impact, and the lithium-ion secondary battery 1 becomes overheated due to a large current flowing due to the short circuit. The "nail penetration test result" column indicates whether or not the lithium-ion secondary battery 1 has "ignited" as a result of this, in other words, the level of the safety margin.
[0080] <Salt concentration in the positive electrode mixture> First, with reference to "Comparative Example 1," "Comparative Example 2," and "Example 1" to "Example 5" in Table 1, the relationship between the concentration of lithium salt 58 contained in positive electrode mixture 51, that is, the "salt concentration" in positive electrode mixture 51, and battery performance will be examined.
[0081] That is, the "salt concentration" in the positive electrode mixture 51 of these "Comparative Example 1", "Comparative Example 2", and "Example 1" to "Example 5" is different from one another. Specifically, the "Comparative Example 1" does not contain lithium salt 58 in the positive electrode mixture 51. In addition, the "salt concentration" in the positive electrode mixture 51 of "Comparative Example 2", "Example 1" to "Example 5" increases in the order of arrangement in Table 1. In addition, in these "Comparative Example 2", "Example 1" to "Example 5", the "acid species" of the organic acid 57 generated by the reaction of the lithium salt 58 contained in the positive electrode mixture 51 with the hydrogen fluoride 54 generated in the electrolyte 41 is all acetic acid 55.
[0082] That is, in these "Comparative Example 2", "Example 1" to "Example 5", when the composite paste 37P is prepared, acetic acid 55 is added as organic acid 57 to react with excess lithium (LiOH) in the positive electrode active material 50. Furthermore, at this time, as shown in the "LiOH amount" and "addition amount" columns in Table 1, the amount of excess lithium present in the positive electrode active material 50 and the amount of acetic acid 55 added are adjusted. As a result, the concentrations of lithium acetate 53 as lithium salt 58 contained in the positive electrode composite 51, that is, the "salt concentration", are different in these "Comparative Example 2", "Example 1" to "Example 5".
[0083] More specifically, the "salt concentration" values (ppm) of "Example 1" to "Example 5" are "27", "585", "1440", "2880", and "4500", respectively, in the order listed in Table 1. The "salt concentration" in "Comparative Example 2" is "less than 10".
[0084] Under these implementation conditions, the "initial resistance," an evaluation index of battery performance, was set to "100%" for "Comparative Example 1," in which the "salt concentration" was "0," and the values for "Comparative Example 2," "Example 1," and "Example 4" were "100-101%," almost the same as "Comparative Example 1." For "Example 4," which had the highest "salt concentration," an increase in "initial resistance" was confirmed up to "105%."
[0085] Furthermore, the "capacity retention rate after 1000 cycles" was "85%" for "Comparative Example 1" and "Comparative Example 2," while it was "87%" for "Example 1," confirming an improvement in performance. And in "Example 2" to "Example 5," which have higher "salt concentrations," the value was "90 to 91%, confirming an even greater improvement in performance.
[0086] In addition, the "resistance increase rate after 1000 cycles" was 10% for "Comparative Example 1" and 12% for "Comparative Example 2," while it was 9% for "Example 1," confirming an improvement in performance. Furthermore, in "Example 2" to "Example 5," which have higher "salt concentrations," the value was 6 to 7%, confirming an even greater improvement in performance. As for the "nail penetration test results," "ignition" was confirmed in "Comparative Example 1" and "Comparative Example 2," while no such "ignition" was confirmed in "Example 1" to "Example 5."
[0087] From the above verification, it has been confirmed that by including in positive electrode mixture 51 lithium salt 58 that reacts with hydrogen fluoride 54 generated in electrolyte solution 41, the battery performance can be improved.
[0088] However, in "Comparative Example 2" in which the "salt concentration" in the positive electrode mixture 51 was the lowest, no significant performance improvement effect was obtained even by containing the lithium salt 58. This suggests that the lower limit of the "salt concentration" is "10 ppm" or more, which is higher than that of "Comparative Example 2". Furthermore, an increase in the "initial resistance" was confirmed in "Example 5" in which the "salt concentration" was the highest. This suggests that the upper limit of the "salt concentration" is a value that does not greatly exceed the value of "4500 ppm" in "Comparative Example 2", for example, about "5000 ppm". And, since a more significant performance improvement effect was obtained in "Example 2" to "Example 4", it is speculated that a more preferable "salt concentration" is in the range of "500 ppm" or more and "3000 ppm" or less, which includes the values of "Example 2" to "Example 4".
[0089] In addition, in "Example 1", in a state in which "0.03 wt%" of excess lithium (LiOH) is present in the positive electrode active material 50, "0.1 equivalent" of acetic acid 55 is added to the positive electrode active material 50, thereby obtaining a "salt concentration" of "27 ppm". Similarly, in "Example 2", in the presence of "0.13 wt%" of excess lithium, "0.5 equivalent" of acetic acid 55 is added, thereby obtaining a "salt concentration" of "585 ppm". And, in "Example 3", in the presence of "0.32 wt%" of excess lithium, "0.5 equivalent" of acetic acid 55 is added, thereby obtaining a "salt concentration" of "1440 ppm".
[0090] Furthermore, in "Example 4", a "salt concentration" of "2880 ppm" was obtained by adding "1 equivalent" of acetic acid 55 in the presence of "0.32 wt%" excess lithium. And in "Example 5", a "salt concentration" of "4500 ppm" was obtained by adding "3 equivalents" of acetic acid 55 in the presence of "0.50 wt%" excess lithium.
[0091] However, in "Comparative Example 2", although "2 equivalents" of acetic acid 55 was added to the positive electrode active material 50, the amount of excess lithium in the positive electrode active material 50 was "less than 0.01 wt%". And, due to this insufficient amount of excess lithium, the "salt concentration" of lithium acetate 53 obtained by the neutralization reaction with the acetic acid 55 remained "less than 10 ppm".
[0092] From the above, in the step of adding organic acid 57 to composite paste 37P to generate lithium salt 58, it is estimated that a preferable amount of surplus lithium is 0.03 wt % or more and 0.5 wt % or less with respect to positive electrode active material 50. In addition, it is estimated that a preferable amount of organic acid 57 to be added is 0.1 equivalents or more and 3 equivalents or less with respect to positive electrode active material 50.
[0093] <Organic acid types> Next, referring to "Comparative Example 3" to "Comparative Example 5" in Table 1, the relationship between the type of organic acid 57 reacted with excess lithium in the positive electrode active material 50 when preparing the composite paste 37P and the battery performance will be examined.
[0094] That is, this "acid species" is the "acid species" of organic acid 57 constituting lithium salt 58 present in positive electrode mixture 51 generated by the above neutralization reaction. When lithium salt 58 contained in positive electrode mixture 51 reacts with hydrogen fluoride 54 generated in electrolyte 41, this becomes the "acid species" of organic acid 57 generated in positive electrode mixture 51.
[0095] Specifically, the "acid species" in "Comparative Example 3" and "Comparative Example 4" is succinic acid, and the "acid species" in "Comparative Example 5" is oxalic acid. Moreover, the "salt concentration" in the positive electrode mixture 51 is different between "Comparative Example 3" and "Comparative Example 4".
[0096] More specifically, in "Comparative Example 3", a "salt concentration" of "1134 ppm" was obtained by adding "1 equivalent" of succinic acid in the presence of "0.13 wt%" excess lithium. In "Comparative Example 4", a "salt concentration" of "13500 ppm" was obtained by adding "3 equivalents" of succinic acid in the presence of "0.50 wt%" excess lithium. And in "Comparative Example 4", a "salt concentration" of "1134 ppm" was obtained by adding "1 equivalent" of oxalic acid in the presence of "0.13 wt%" excess lithium.
[0097] In addition, the acid dissociation constant (pKa) of succinic acid is 4.2, and the acid dissociation constant of oxalic acid is 1.27. The boiling point of succinic acid is over 190°C, and oxalic acid decomposes at 190°C.
[0098] Under these implementation conditions, the "initial resistance," an evaluation index of battery performance, was confirmed to have increased significantly from "100%" for "Comparative Example 3" to "120%" for "Comparative Example 4" with a high "salt concentration." The "initial resistance" of "Comparative Example 5" was "102%."
[0099] Moreover, the "capacity maintenance rate after 1000 cycles" was "90%" for "Comparative Example 3", "91%" for "Comparative Example 4", and "83%" for "Comparative Example 5". Furthermore, the "resistance increase rate after 1000 cycles" was "7%" for "Comparative Example 3", "6%" for "Comparative Example 4", and "15%" for "Comparative Example 5". As for the "nail penetration test results", "ignition" was confirmed in all of "Comparative Example 3" to "Comparative Example 5".
[0100] As described above, in "Comparative Example 3" and "Comparative Example 4" in which the "acid species" is succinic acid, the performance improvement effect of the lithium ion secondary battery 1 due to the inclusion of lithium salt 58 in the positive electrode mixture 51 was confirmed, although it was more limited than when acetic acid 55 was used as the "acid species". However, in "Comparative Example 5" in which the "acid species" is oxalic acid, the performance improvement effect was not confirmed. This suggests that the lithium salt 58 generated in the positive electrode mixture 51 by the neutralization reaction between the oxalic acid added to the mixture paste 37P and the excess lithium in the positive electrode active material 50, that is, lithium oxalate, did not react with the hydrogen fluoride 54 generated in the electrolyte 41.
[0101] That is, in "Comparative Example 3" and "Comparative Example 4" in which succinic acid having an "acid dissociation constant" of 3.15 or more is used as the "acid species," a weak acid liberation reaction proceeds between lithium salt 58 generated in positive electrode mixture 51 by the neutralization reaction, that is, lithium succinate, and hydrogen fluoride 54 generated in electrolyte 41. As a result, hydrogen fluoride 54 generated in electrolyte 41 is consumed, and the performance of lithium ion secondary battery 1 is improved.
[0102] In contrast, in "Comparative Example 5" in which oxalic acid having an "acid dissociation constant" lower than 3.15 is used as the "acid species," the weak acid liberation reaction between lithium oxalate produced in positive electrode mixture 51 by the neutralization reaction and hydrogen fluoride 54 produced in electrolyte 41 does not proceed. As a result, it is presumed that hydrogen fluoride 54 produced in electrolyte 41 remains as it is, causing a gradual decrease in the performance of lithium ion secondary battery 1.
[0103] Also, in "Comparative Example 3" and "Comparative Example 4" which also use succinic acid as the "acid species", the "initial resistance" value is deteriorated in "Comparative Example 4" which has a high "salt concentration". This suggests that when the "salt concentration" is too high, lithium salt 58 in positive electrode mixture 51 inhibits the battery reaction.
[0104] That is, while the "salt concentration" of "Comparative Example 3" is within the range of "10 ppm to 5000 ppm" which is the "preferable range" when the "acid species" is acetic acid 55, the value of "Comparative Example 3" is significantly higher than this range. Furthermore, the "salt concentration" of "Comparative Example 3" is within the range of "500 ppm to 3000 ppm" which is the "more preferable range" when the "acid species" is acetic acid 55. Therefore, even when an "acid species" other than acetic acid 55 is used, the "salt concentration" is preferably within the range of "10 ppm to 5000 ppm", and more preferably within the range of "500 ppm to 3000 ppm".
[0105] Furthermore, the reason why "ignition" was confirmed in "Comparative Example 3" and "Comparative Example 4" in the "nail penetration test" is presumably because the boiling point of succinic acid is higher than that of acetic acid 55. That is, when the "acid species" is succinic acid, succinic acid as organic acid 57 in electrolyte 41 generated by the weak acid liberation reaction with hydrogen fluoride 54 is difficult to vaporize. As a result, it is considered that the generated bubbles are difficult to wrap around the positive electrode active material 50, and therefore the generation of a large current that leads to the "ignition" could not be suppressed.
[0106] <Fluorine-based additives> Next, with reference to "Comparative Example 6", "Comparative Example 7", and "Example 6" to "Example 9" in Table 1, the case where electrolytic solution 41 contains a fluorine-based additive will be examined.
[0107] In "Comparative Example 6", "Example 6", and "Example 7", fluoroethylene carbide (FEC) is contained as an additive in the electrolyte 41. In "Comparative Example 7", "Example 8", and "Example 9", fluorosulfonic acid (FSO) is contained as an additive in the electrolyte 41. In these comparative examples and examples, "FSO" is added to the electrolyte 41 in the form of a lithium salt, that is, as lithium fluorosulfonate. In other words, these two additives are both fluorine compounds having one fluorine atom in one molecule. In addition, "Comparative Example 6" and "Comparative Example 7" do not contain lithium salt 58 in the positive electrode mixture 51. In addition, "Example 6" and "Example 7", and "Example 8" and "Example 9", respectively, have different "salt concentrations" in the positive electrode mixture 51.
[0108] Specifically, in "Example 6", a "salt concentration" of "1134 ppm" was obtained by adding "1 equivalent" of acetic acid 55 in the presence of "0.13 wt%" excess lithium. In "Example 7", a "salt concentration" of "81 ppm" was obtained by adding "0.3 equivalent" of acetic acid 55 in the presence of "0.03 wt%" excess lithium. Furthermore, in "Example 8", a "salt concentration" of "1170 ppm" was obtained by adding "1 equivalent" of acetic acid 55 in the presence of "0.13 wt%" excess lithium. And, in "Example 9", a "salt concentration" of "81 ppm" was obtained by adding "0.3 equivalent" of acetic acid 55 in the presence of "0.03 wt%" excess lithium.
[0109] Under these implementation conditions, when "FEC" was contained as an additive in the electrolyte 41, the "initial resistance", which is an evaluation index of the battery performance, was "100%" for "Comparative Example 6" and "Example 6" and "Example 7", respectively, and "101%" for both. Similarly, when "FSO" was contained as an additive in the electrolyte 41, the "initial resistance" was "100%" for "Comparative Example 7" and "Example 8" and "Example 9", respectively, and "101%" for both.
[0110] Moreover, the "resistance increase rate after 1000 cycles" was "91%" for "Comparative Example 6", "96%" for "Example 6", and "92%" for "Example 7". Furthermore, it was "90%" for "Comparative Example 7", "95%" for "Example 8", and "91%" for "Example 9". Regarding the "nail penetration test results", "ignition" was confirmed in "Comparative Example 6" and "Comparative Example 7" which did not contain lithium salt 58 in positive electrode mixture 51, but such "ignition" was not confirmed in any of "Examples 6" to "Examples 9" which contained lithium salt 58.
[0111] As described above, it has been confirmed that even when electrolyte 41 contains a fluorine-based additive, by including lithium salt 58 in positive electrode mixture 51, the performance of lithium ion secondary battery 1 is improved.
[0112] Regarding the "salt concentration" in the positive electrode mixture 51, when the electrolyte solution 41 contained "FEC" as an additive, "Example 6" having a higher "salt concentration" had a higher performance improvement effect than "Example 7" having a lower "salt concentration". Similarly, when the electrolyte solution 41 contained "FSO" as an additive, "Example 8" having a higher "salt concentration" had a higher performance improvement effect than "Example 9" having a lower "salt concentration".
[0113] Furthermore, since the values of the lower "salt concentration" in "Example 7" and "Example 9" in these Examples are both "81 ppm," it is presumed that the "preferable salt concentration range" when the electrolyte 41 contains a fluorine-based additive is, for example, "80 ppm" or more. And, it is presumed that the "more preferable range" of the "salt concentration" is, for example, "100 ppm" or more.
[0114] Incidentally, it is considered that the upper limit value of the "preferable salt concentration range" can be referenced to the upper limit value in the case where the electrolyte 41 does not contain a fluorine-based additive. Therefore, even in the case where the electrolyte 41 contains a fluorine-based additive, the "preferable range" of the "salt concentration" is presumed to be, for example, "5000 ppm" or less. Furthermore, the "more preferable range" is presumed to be, for example, "3000 ppm" or less. And, as for the lower limit value of the "preferable salt concentration range", by reference to the value in the case where the electrolyte 41 does not contain a fluorine-based additive, the further "preferable range" is presumed to be, for example, "500 ppm" or more.
[0115] Next, the technical ideas that can be understood from the above embodiment and modified examples will be described. (i) A lithium ion secondary battery in which the additive is lithium fluorosulfonate. (b) A lithium ion secondary battery in which the additive is fluoroethylene carbide.
[0116] (c) A method for producing a lithium ion secondary battery, wherein the excess lithium is lithium hydroxide. (iv) A method for manufacturing a lithium ion secondary battery, comprising the step of removing the organic acid remaining in the composite paste by raising the temperature to or above the boiling point of the organic acid when drying the composite paste applied to the base material, thereby making it possible to easily remove the organic acid remaining in the composite paste after the reaction with the excess lithium of the positive electrode active material with a simple configuration. [Explanation of symbols]
[0117] 1...Lithium-ion secondary battery 41...Electrolyte 50...Cathode active material 51...Positive electrode mixture 54…Hydrogen fluoride 57...Organic acid 58...Lithium salt
Claims
1. In the positive electrode mixture containing the positive electrode active material, LiPF 6 and reacting with hydrogen fluoride produced in the electrolyte to produce acetic acid having an acid dissociation constant of 4.76 when water is used as a medium, the acid dissociation constant being relatively weaker than hydrogen fluoride. 3 COOLi is contained in the positive electrode mixture, 3 A lithium ion secondary battery having a COOLi concentration of 500 ppm or more and 3000 ppm or less.
2. The boiling point of the acetic acid is equal to or lower than the melting point of the separator. The lithium ion secondary battery according to claim 1 .
3. A method for producing a lithium ion secondary battery, comprising applying a composite paste containing a positive electrode active material to a substrate serving as a current collector to form a positive electrode composite layer on the substrate, the method comprising the steps of: When preparing the composite paste, acetic acid having an equivalent weight of 0.5 or more and 1 or less with respect to the positive electrode active material is added, LiPF 6 By reacting with hydrogen fluoride generated in an electrolyte solution containing CH 3 COOLi is added to the mixture paste, and the CH 3 A method for manufacturing a lithium ion secondary battery, comprising the step of adjusting the concentration of COOLi to 500 ppm or more and 3000 ppm or less.
Citation Information
Patent Citations
Lithium ion secondary battery
JP2010135190A
Nonaqueous electrolyte and nonaqueous electrolyte secondary battery employing the same
JP2016186915A
Method for manufacturing positive electrode
JP2019079710A
Method for manufacturing positive electrode for nonaqueous electrolyte lithium secondary battery
JP2019164960A
Positive electrode composition
JP2021163626A